Evaluation of Pest Control of Oryctes Rhinoceros Using Pheromonas and Light Trap Methods in Palm Oil Plantation Companies - Andi Lelanovita Sardianti; Nur Asikin; Sri Ngapiyatun; Rossy Mirasari; Arief Rahman; Muhamad Yazid Bustomi (Politeknik Pertanian Negeri Samarinda, 2026)
Oryctes rhinoceros is a major pest of oil palm plantations, frequently causing serious physical damage, such as holes in stems and fronds, which can inhibit plant growth and development. The presence of this pest, especially on young plants, can reduce productivity and potentially cause significant economic losses for plantation companies.This study aimed to evaluate the effectiveness of two Oryctes rhinoceros pest control methods, namely the Pheromonas method and the Light Trap method, applied in oil palm plantations. The evaluation was based on the number of pest captures obtained during a 28-day observation period. The results showed that the Pheromonas method was considered effective because the number of pest captures exceeded the control threshold, which was more than 20 individuals per hectare per month. Conversely, the Light Trap method did not show optimal results, as the number of captures remained below this threshold. This indicates that Pheromonas is more effective at attracting and capturing pests than Light Traps under the environmental conditions of this study.